Microbial Profile in Paediatric Patients with Wound Infection and Their Antibiotic Susceptibility Pattern (Community Based Medical Journal, 2025)
Wound infection is one of the major health problems that frequently occur among patients reporting or admitted in the hospital. This observational study was conducted in the Department of Microbiology at Bangladesh Shishu Hospital and Institute, Dhaka, Bangladesh, between November 2023 and May 2024, to observe the microbial profile in paediatric patients with wound infection and their antibiotic susceptibility pattern. A total of 372 wound swabs were collected and analyzed by using culture and antibiotic sensitivity tests. From total wound swab samples, culture positive samples were 281(75.54%). Among those, 52(18.5%) were Gram-positive and 229(81.5%) were Gram negative. Pseudomonas spp was the most commonly 83(36.24%) isolated organisms, followed by Escherechia coli 48(20.96%), Acinetobacter spp 33(14.41%), Klebsiella spp 24(10.48%) among Gram-negative bacteria. On the other hand, Staphylococcus spp 23(44%) was the most prevalent, followed by Staphylococcus aerues 18(35%) among Gram-positive isolates. 94% of the isolated Staphylococcus aerues were methicillin resistant Staphylococcus aerues (MRSA). Staphylococcus spp showed higher resistant pattern against azithromycin (91%), erythromycin (91%), linezolid (78%), ciprofloxacin (69%), moxifloxacin (65%), levofloxacin (52%) and gentamycin (52%). Most of the Gram-negative bacteria showed higher resistant against ampicillin followed by third and fourth generation cephalosporins, fluroquinolones. Periodic surveillance of microbial profile and appropriate antibiotic selection are necessary to prevent multidrug resistant bacteria in hospital patients. Moreover, infection prevention campaigns must be strengthened among hospital wards and premises.  CBMJ 2025 January: Vol. 14 No. 01 P: 46-53